2021
DOI: 10.1002/lt.26071
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Visceral Adiposity as a Predictor for Resolution of Nonalcoholic Fatty Liver in Potential Living Liver Donors

Abstract: This study aimed to determine the factors associated with resolution of nonalcoholic fatty liver (NAFL) after lifestyle intervention in potential living liver donors as assessed by the gold standards in a longitudinal setting. This retrospective study included 115 potential living liver donors (mean age, 30.5 ± 7.5 years; 101 men) with NAFL who underwent paired liver biopsies and abdominal computed tomography (CT) examinations before and after lifestyle intervention between January 2011 and December 2018. Anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Based on two studies ( 19 , 20 ) with 85 patients, we found a pooled correlation coefficient of r = 0.49 (CI: 0.22–0.69, Spearman's correlation) between VAT change and liver steatosis. Similarly, based on three ( 21 , 23 , 27 ) studies with 175 patients, the correlation was r = 0.33 (0.19–0.46, Pearson's correlation, Figure 2 ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on two studies ( 19 , 20 ) with 85 patients, we found a pooled correlation coefficient of r = 0.49 (CI: 0.22–0.69, Spearman's correlation) between VAT change and liver steatosis. Similarly, based on three ( 21 , 23 , 27 ) studies with 175 patients, the correlation was r = 0.33 (0.19–0.46, Pearson's correlation, Figure 2 ).…”
Section: Resultsmentioning
confidence: 84%
“…In the multivariate Cox proportional hazard model, the risk for regressed NAFLD comparing tertiles 2 and 3 vs. tertile 1 of change in VAT area were hazard ratio (HR) = 0.70 (CI: 0.42–1.16) and HR = 0.38 (CI: 0.20–0.73), respectively. Lee et al ( 27 ) examined the effect of lifestyle interventions in living liver donors with NAFLD on the improvement of different body composition parameters and changes in steatosis. The relative reduction of the visceral fat area was the only significant independent factor associated with resolved NAFLD (odds ratio—OR = 1.03, CI: 1.01–1.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study found that NAFLD significantly resolved (less than 5% hepatic steatosis on follow-up liver biopsy) after lifestyle intervention to reduce visceral fat area. 35 In addition, weight loss helps to improve NAFLD. Bariatric surgery is an effective way to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…Another question we considered was whether reducing visceral fat would contribute to the regression of NAFLD. A retrospective study found that NAFLD significantly resolved (less than 5% hepatic steatosis on follow‐up liver biopsy) after lifestyle intervention to reduce visceral fat area 35 . In addition, weight loss helps to improve NAFLD.…”
Section: Discussionmentioning
confidence: 99%